A DEVELOPMENT OF PRACTICUM INSTRUCTIONS BASED ON QR CODE - Andi Norhaedah; Vandalita MM Rambitan; Sonja VT Lumowa (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2020)
Low mastery of concepts and science process skills of students into the background in the development of the book practicum -based QR code. Based on the observations of the VIII grade science teachers at Public Middle School 2, Public Middle School 6, Public Middle School 4, Public Middle School 1, and Public Middle School 22 Samarinda, it was found that 75% of science practicum had not focused on biology and 62% of learning activities still tended to be conventional. In addition, the average science learning outcomes of students at this junior high school were sufficient . The purpose of this study was to determine the validity, practicality, and effectiveness of the QR code-based practical manual in improving students 'mastery of concepts and students' science process skills. The samples in this analysis were students and science teachers of Biology and students of Public Middle School 2 Samarinda . Results of research show as much as 96.17 % of validity 98.63% of material and material validity of the validator. The practicality results of the QR code-based practicum manual were 95.09%, the results of students 'mastery of concepts were 8437%, and the results of students' science process skills were 85.59%. Based on the results of the validity, practicality, and effectiveness of Biology students and teachers at Public Middle School 2 Samarinda, it can be concluded that the QR code-based practicum manual on Biology Science learning is suitable for use as a practical learning media .